Transition to family parenting in the face of the first child: a scoping review - Maria Isabel Ventura Araújo; Alberto Carlos Marques Duarte; Maria Henriqueta de Jesus Silva Figueiredo; Carmen Maria da Silva Maciel Andrade (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify and summarize the elements that characterize the family transition process in relation to the first child. Methods: a scoping review was carried out based on JBI methodology, in six databases, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews checklist. Results: ten articles were included with factors characterizing the transition, such as hindering/facilitating conditions that influence the process, important support structures in adaptation and strategies/responses used in the transition process. Final Considerations: elements characterizing the transition process in relation to the first child were identified. However, no theoretical explanation for this was identified. Further research should be carried out to obtain a deeper understanding of this process.